2017
DOI: 10.1002/ase.1757
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study in learning preferences and academic performance in first year medical school

Abstract: This is a longitudinal study of first year medical students that investigates the relationship between the pattern change of the learning preferences and academic performance. Using the visual, auditory, reading-writing, and kinesthetic inventory at the beginning of the first and second year for the same class, it was found that within the first year, 36% of the class remained unimodal (single) modality learners (SS), 14% changed from unimodal to multimodality learners (SM), 27% changed from multimodality to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The learning style of each individual is a component of these four basic forms; however, recent reviews show that the Kolb LSI is not supported by well-designed studies, and only a few studies have shown statistically significant results for some subjects (Rohrer and Pashler, 2012). In this study, the Kolb LSI was used as part of the randomization procedure because it has been found that medical students' Kolb scores may change during their medical education (Gurpinar et al, 2011;Bitran et al, 2012;Hu et al, 2018).…”
Section: Randomization Proceduresmentioning
confidence: 98%
“…The learning style of each individual is a component of these four basic forms; however, recent reviews show that the Kolb LSI is not supported by well-designed studies, and only a few studies have shown statistically significant results for some subjects (Rohrer and Pashler, 2012). In this study, the Kolb LSI was used as part of the randomization procedure because it has been found that medical students' Kolb scores may change during their medical education (Gurpinar et al, 2011;Bitran et al, 2012;Hu et al, 2018).…”
Section: Randomization Proceduresmentioning
confidence: 98%
“…In previous studies, study preference primarily referred to sensory modality preferences. This denotes those students make study choices physically, through vision or auditory reactions (Hu et al, 2018 ). However, the study preferences in this research primarily referred to students' psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanation behind the parallel long-term performance of both groups could be loss of retained knowledge among the multimodal group of learners. Recently, a study has found that transition of learning style occurs over the course of the teaching and transition of unimodal to multimodal learners improved their academic performance [26]. Previous studies have stated that identifying the learning style could enable the teachers in designing the curriculum to match the teaching modalities [1011].…”
Section: Discussionmentioning
confidence: 99%